A highly oriented poly(3, 4‐ethylenedioxythiophene) film: Facile synthesis and application for supercapacitor. Issue 20 (15th February 2016) - Yang, Huan; Liu, Ye; Wang, Zhongde; Liu, Yiming; Du, Haiyan; Hao, Xiaogang
ABSTRACT: A single crystal poly(3, 4‐ethylenedioxythiophene) (PEDOT) film with highly oriented arrangement has been fabricated from an aqueous solution by a novel unipolar pulse electropolymerization method. Film formation mechanism was proposed based on the in situ mass change during electropolymerization process measured by the electrochemical quartz crystal microbalance. The compositions, morphology and crystal structure of the fabricated films are characterized by Fourier transfer infrared spectroscopy, scanning electron microscopy, and X‐ray diffraction, respectively. It is found that the prepared PEDOT film on carbon nanotubes (CNTs)‐modified electrode with a spongy dendritic structure possesses outstanding electroactivity, high specific capacitances (239.1 F⋅g −1, including the specific capacitances of CNTs which is 21.4 F⋅g −1 ), and excellent cycling stability with 7.3% decay from its initial capacitance over 10, 000 cycles. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43418. Abstract :